La costruzione sociale dell’immigrazione come problema: il caso italiano - Pilati, Katia (SocietàMutamentoPolitica, 2018)
The objective of this article is to examine categories and meanings associated to migration in the Italian public discourse. With this purpose we analyze public claims-makings – discursive interventions as well as political actions – by various institutional and non-institutional actors in the field of migration. We analyze claims in Milan contained in the articles of La Repubblica (2006) drawing on political claims analysis, a specification of protest event analysis (PEA). Results show a closure of the discursive opportunity structure (DOS): radical right groups are the main actors claiming against immigration, contributing to build immigration as a social problem by emphasizing issues such as the cultural menace and religious clash associated to migration; there is a high percentage of neutral positions among parties such as Forza Italia as well as in the center-left coalition; migrant groups show low levels of public claims-makings, confirming their marginalization from the Italian public discourse.